2010
DOI: 10.5194/bg-7-1877-2010
|View full text |Cite
|
Sign up to set email alerts
|

Fire dynamics during the 20th century simulated by the Community Land Model

Abstract: Abstract.Fire is an integral Earth System process that interacts with climate in multiple ways. Here we assessed the parametrization of fires in the Community Land Model (CLM-CN) and improved the ability of the model to reproduce contemporary global patterns of burned areas and fire emissions. In addition to wildfires we extended CLM-CN to account for fires related to deforestation. We compared contemporary fire carbon emissions predicted by the model to satellite-based estimates in terms of magnitude and spat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
361
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(392 citation statements)
references
References 86 publications
23
361
4
Order By: Relevance
“…Estimates from this study using the future scenarios analyzed in the IPCC (the Representative Concentration Pathway, RCP, scenarios) suggest between 20 and 210 PgC carbon will be released, consistent with Strassmann et al (2008), and at the higher end of the model range reported by Brovkin et al (2013). Our model underpredicts the uptake of land carbon relative to other models (e.g Arora et al, 2013), and unlike other estimates includes the explicit interplay between changes in land use and fires (e.g., Marlon et al, 2008;Kloster et al, 2010). The RCP scenarios were designed to cover a diverse set of pathways and create a broad range in possible outcomes for the next century (Moss et al, 2010).…”
Section: Enhancement Of Land Use Co 2 Radiative Forcingmentioning
confidence: 65%
See 2 more Smart Citations
“…Estimates from this study using the future scenarios analyzed in the IPCC (the Representative Concentration Pathway, RCP, scenarios) suggest between 20 and 210 PgC carbon will be released, consistent with Strassmann et al (2008), and at the higher end of the model range reported by Brovkin et al (2013). Our model underpredicts the uptake of land carbon relative to other models (e.g Arora et al, 2013), and unlike other estimates includes the explicit interplay between changes in land use and fires (e.g., Marlon et al, 2008;Kloster et al, 2010). The RCP scenarios were designed to cover a diverse set of pathways and create a broad range in possible outcomes for the next century (Moss et al, 2010).…”
Section: Enhancement Of Land Use Co 2 Radiative Forcingmentioning
confidence: 65%
“…This configuration of CLM simulates the complicated interplay between land use, land use change, fires, land carbon uptake and loss, and emissions of volatile organic compounds (Thornton et al, 2009;Kloster et al, 2010;Guenther et al, 2006). To isolate the impacts of LULCC we perform separate…”
Section: Lulcc Emissions (Computed From Clm)mentioning
confidence: 99%
See 1 more Smart Citation
“…A promising recent trend is the development of fire modules within DGVMs [Arora and Boer, 2005;Lenihan et al, 2008;Kloster et al, 2010;Thornicke et al, 2010;Prentice et al, 2011;Li et al, 2012]. With their relatively coarse time steps and spatial resolution, DGVM-based fire modules are compelled to do enough "averaging" to avoid the pitfalls of trying to pin down a stochastic process too precisely.…”
Section: Predicting Firementioning
confidence: 99%
“…Fire, extreme drought, insect outbreaks, land management, and land cover and land use change influence terrestrial C dynamics via (1) altering rate processes, for example, gross primary productivity (GPP), growth, tree mortality, or heterotrophic respiration; (2) modifying microclimatic environments; or (3) transferring C from one pool to another (e.g., from live to dead pools during storms or release to the atmosphere with fire) (Kloster et al, 2010;Thonicke et al, 2010;Luo and Weng, 2011;Prentice et al, 2011;Weng et al, 2012). Those disturbance influences can be represented in terrestrial C cycle models through changes in parameter values, environmental scalars, and/or discrete C transfers among pools of Eq.…”
Section: Assumptions Of the C Cycle Models And Validity Of This Analysismentioning
confidence: 99%